SMP ISLAM TERPADU INSAN MADANI BANJARMASIN - Annadiana, Annadiana; wastuty, Prima widia (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
The increasing number of population citizens in Banjarmasin from year to year has an effect on the increasing need for educational facilities, in terms of quality and quantity. Besides the government, the private sector also provides formal education facilities. Insan Madani Integrated Islamic Junior High School Banjarmasin is one of the private schools in Banjarmasin. But the Bina Insan Madani Foundation has not provided a school building that complies with government standards. It is necessary to design Insan Madani Integrated Islamic Junior High School Banjarmasin in accordance with the standards and create an educational atmosphere that can support the learning process. The Architectural Programming method of William Pena was chosen to solve the architectural problem. The Qur’an Educative Space Concept is a design of SMPIT Insan Madani Banjarmasin which makes every room in this school a place of learning. Qur’an Educative space is applied to outer space and inner space, so students can study in every room and memorize the Qur’an well in the school